(untitled) (The Pakistan Development Review, 2004)
Nearly one-quarter of Pakistan’s Gross Domestic Product (GDP) is contributed by the agriculture sector and it employs nearly 44 percent of the labour force. Agricultural exports, directly and indirectly, make up a large proportion of total exports and foreign exchange earnings of the country. Agriculture in Pakistan faces considerable challenge in the 21st century. The present population of about 149 million, growing at about 1ta. 9 percent per year, is expected to double to 298 million in about 40 years. Pakistan’s agriculture has experienced rapid growth since the 1960s. The average annual growth of about 4 percent in the four decades before the onset of the new millennium has exceeded the population growth that touched about 3 percent for a substantial part of this period.1 This rate of growth in agriculture has been sustained by the technological progress embodied in the highyielding varieties of grains and cotton with supporting public investment in irrigation, agricultural research and extension (R&E), and physical infrastructure. Agricultural growth, in turn, has made significant contribution to the overall economic growth of about 6 percent per year during this period. Despite rising per capita income, food demand is likely to grow rapidly given the low level of current per capita income. There is a compelling need for sustained efforts to increase production of essential items (wheat, edible oils, etc.). Faced with limits to further expansion of cultivated land and slowing returns to further input intensification, productivity growth assumes a central role in meeting the challenges of the future.